Pengaruh volume Zn terhadap kekerasan dan struktur mikro pada friction stir processing aluminium AA 1100 - Alvia Restu Putra Utama; Nurul Muhayat; T Triyono (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
Friction Stir Processing (FSP) is a development of FSW mechanism on surface hardening process such as in aluminium. The using of aluminium and its alloy were globally used as machining part, it because aluminium and its alloy are light and able to forming. Goal of this study are learn the effect of Zn volume on mechanical and physical properties of aluminium alloy 1100. Mechanical properties are tested by the Vickers Hardness Testing, while the physical properties are observe by macrostructures testing, microstructures testing and SEM. The variation are 22 mm3, 45 mm3, 67 mm3, 90 mm3 of Zn volume and without Zn. Rotating speed of tool, dwell time, and plunge depth are in same conditions. Observation result of SEM and mapping show that Zn were not spread well on SAZ. This condition prove by the high of Zn in the edge zone of tool by EDS observation. The result of hardness testing show that the increasing of Zn volume will increase the hardness properties. The highest result of hardness testing in FSP AA1100 is 87.5 HV with the most Zn volume variation, while without Zn is 44.7 HV.